IRTree models with ordinal and multidimensional decision nodes for response styles and trait‐based rating responses. (12th February 2019) - Meiser, Thorsten; Plieninger, Hansjörg; Henninger, Mirka
Abstract : IRTree models decompose observed rating responses into sequences of theory‐based decision nodes, and they provide a flexible framework for analysing trait‐related judgements and response styles. However, most previous applications of IRTree models have been limited to binary decision nodes that reflect qualitatively distinct and unidimensional judgement processes. The present research extends the family of IRTree models for the analysis of response styles to ordinal judgement processes for polytomous decisions and to multidimensional parametrizations of decision nodes. The integration of ordinal judgement processes overcomes the limitation to binary nodes, and it allows researchers to test whether decisions reflect qualitatively distinct response processes or gradual steps on a joint latent continuum. The extension to multidimensional node models enables researchers to specify multiple judgement processes that simultaneously affect the decision between competing response options. Empirical applications highlight the roles of extreme and midpoint response style in rating judgements and show that judgement processes are moderated by different response formats. Model applications with multidimensional decision nodes reveal that decisions among rating categories are jointly informed by trait‐related processes and response styles.